Maxims of equity : a juridical critique of the ethics of equity law in Great Britain - Levenstein, Michael David (Algora Publishing, 2014)
This monograph on British Equity Law (that branch which deals with wills, probate, trust funds and land law) discusses the philosophical underpinnings of the 'Maxims of Equity' - twenty or so guiding principles which attempt to ameliorate the rigor of the common law, and to discuss these principles in light of both jurisprudential philosophy and actual case law. Equity is a world unto itself. Originally conceived and administered by the ancient Court of Chancery in England, this arcane body of rules and principles has matured into a distinct branch of modern jurisprudence, influencing almost e.